2020
DOI: 10.1371/journal.pone.0234233
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted interventions for healthcare-associated infections and rational use of antibiotics in a low-to-middle-income country: Can they be sustained?

Abstract: Background Transmission of infection between patients by health workers, and the irrational use of antibiotics are preventable causes for healthcare-associated infections (HAI) and multi-resistant organisms. A previous study implementing a hand hygiene campaign and antibiotic stewardship program significantly reduced these infections. Sustaining such interventions can be challenging. Aims To evaluate whether there was a sustained effect of a multifaceted infection control and antibiotic stewardship program on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
0
11
0
1
Order By: Relevance
“…A prospective cohort study was conducted in the PICU and general pediatric wards at Dr Sardjito Hospital in Yogyakarta, Indonesia during 1st June 2016 to 31st December 2019 [ 11 ]. The Dr. Sardjito Hospital is a referral hospital for Yogyakarta and the Southern part of the Central Java provinces in Indonesia, and provides services to a population of approximately 3.5 million people.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective cohort study was conducted in the PICU and general pediatric wards at Dr Sardjito Hospital in Yogyakarta, Indonesia during 1st June 2016 to 31st December 2019 [ 11 ]. The Dr. Sardjito Hospital is a referral hospital for Yogyakarta and the Southern part of the Central Java provinces in Indonesia, and provides services to a population of approximately 3.5 million people.…”
Section: Methodsmentioning
confidence: 99%
“…The definitions of HAI were based on the US Centers for Disease Control and Prevention (CDC) National Healthcare Safety Network (NHSN) and the National Nosocomial Infections Surveillance (NNIS) system. Every child in the study was observed each day to see whether he/she fulfilled the CDC criteria for a HAI [ 11 , 12 ]. Investigations of the causes of fever and other signs of infection were at the discretion of the treating clinical staff.…”
Section: Methodsmentioning
confidence: 99%
“…However, the current understanding of the drivers of hand hygiene behaviours specific to labour and delivery is limited [ 12 , 13 ]. Hand hygiene improvement strategies targeting HCW often result in small or moderate effects [ 12 , 22 ] and are often only short-term [ 13 , 23 ]. Current approaches to improving hand hygiene practices among HCW largely focus on a limited set of known behavioural determinants (knowledge, skills, and physical opportunity), provide limited information on the specific determinants interventions target, or address hand hygiene as part of a generalized set of hygiene behaviours [ 18 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 45 mothers were observed; 22 from the PHC and 23 from the RH. Mothers from the PHC and RH had similar characteristics with a mean age of 28 (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) and had an average of 2 (0-6) previous live births. The average travel time to the HCF was 19 minutes .…”
Section: Participant Informationmentioning
confidence: 99%
“…However, the current understanding of the drivers of hand hygiene behaviours speci c to labour and delivery is limited (12,13). Hand hygiene improvement strategies targeting HCW often result in small or moderate effects (12,22) and are often only short-term (13,23). Current approaches to improving hand hygiene practices among HCW largely focus on a limited set of known behavioural determinants (knowledge, skills, and physical opportunity), provide limited information on the speci c determinants interventions target, or address hand hygiene as part of a generalized set of hygiene behaviours (18,24).…”
mentioning
confidence: 99%